PERBAIKAN BEBERAPA SIFAT FISIK TANAH DAN HASIL TANAMAN JAGUNG DENGAN PEMBERIAN VERMIKOMPOS DAN KOMPOS LIMBAH JAGUNG PADA ENTISOLS PESISIR: - Marfu’ah Darodjah; Bambang Gonggo Murcitro; Heru Widiyono; Bambang Sulistyo; Elsa Lolita Putri (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[IMPROVEMENT OF SELECTED SOIL PHYSICAL PROPERTIES AND CORN YIELD THROUGH THE APPLICATION OF VERMICOMPOST AND CORN WASTE COMPOST ON COASTAL ENTISOLS]. The growth and productivity of corn are less than optimal on marginal soils such as Entisols. To improve these outcomes, soil physical properties can be enhanced by adding organic matter. This study aims to determine the best dosage of vermicompost and corn waste compost to improve several physical soil properties and corn yields in coastal Entisols. The research method used was a randomized block design (RCBD) with two factors. The first factor was the dosage of organic fertilizer at five levels: 0, 5, 10, 15, and 20 tons/ha. The second factor was the type of organic fertilizer, vermicompost and corn waste compost. Each treatment was repeated three times, resulting in 30 experimental units. The research variables included soil moisture content, bulk density, soil porosity, dry biomass weight, dry shelled corn weight, ear weight with husk, and ear weight without husk. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level. If significant differences were found, further testing was carried out using the DMRT test. The results showed that the most optimal dosage of organic fertilizer for improving soil physical properties and increasing corn yields was 15-20 tons/ha. At this dosage, there was a significant improvement in several soil physical properties and corn yield parameters, including dry biomass weight, ear weight with husk, ear weight without husk, and dry shelled corn weight. The 15-20 tons/ha dosage not only improved soil moisture content, bulk density, and soil porosity but also substantially increased corn productivity. The use of vermicompost and corn waste compost proved effective in enhancing soil fertility and crop yields, making it a sustainable and environmentally friendly alternative for agriculture in coastal areas.